Immune Responses to Plasma-Derived Versus Recombinant FVIII Products - Peyvandi, Flora; Miri, Syna; Garagiola, Isabella (Frontiers in Immunology, 2021)
The most severe side effect of haemophilia treatment is the inhibitor development occurring in 30% of patients, during the earliest stages of treatment with factor (F)VIII concentrates. These catastrophic immune responses rapidly inactivate the infused FVIII, rendering the treatment ineffective. This complication is associated with a substantial morbidity and mortality. The risk factors involved in the onset of the inhibitors are both genetic and environmental. The source of FVIII products, i.e. plasma-derived or recombinant FVIII products, is considered one of the most relevant factors for inhibitor development. Numerous studies in the literature report conflicting data on the different immunogenicity of the products. Conclusive data on the increased immunogenicity of recombinant products was obtained from the SIPPET randomised trial, where patients treated with recombinant FVIII products had an 87% higher risk to develop inhibitors than those treated with plasma-derived products in the first exposure days. The potential increase in the immunogenicity of recombinant products can be attributed to several factors such as: the different post-translational modification in different cell lines, the presence of protein aggregates, and the role played by the chaperon protein of FVIII, the von Willebrand factor, which modulates the uptake of FVIII by antigen presenting cells (APCs). Furthermore, the presence of non-neutralising antibodies against FVIII has shown to be associated with increased development of inhibitors as demonstrated in a sub-analysis of the SIPPET study. In addition, the presence of the specific subclasses of the immunoglobulins may also be an important biomarker to indicate whether the inhibitor will evolve into a persistent neutralising antibody or a transient one that would disappear without any specific treatment. Recently, the availability of novel non-replacement therapies as well as Hemlibra, administered by weekly subcutaneous infusion, have significantly changed the quality of life of patients with inhibitors showing a considerable reduction of the annual bleeding rate and in most patients the absence of bleeding. Although, these novel drugs improve patients’ quality of life, they do not abolish the need to infuse FVIII during acute bleeding or surgery. Therefore, the issue of immunogenicity against FVIII still remains an important side effect of haemophilia treatment.